Validity of differentiated ratings of perceived exertion for use during aquatic cycling - Fontanari, P.; Tartaruga, P.; Caron, O. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Although aquabiking has become widespread, the assessment of the intensity for aquatic cycling remains poorly defined. METHODS: This study investigated the validity of differentiated ratings of perceived exertion (dRPE) recorded from the chest (RPE-chest) and legs (RPE-legs) during aquatic cycling and aimed to determine a simple and accurate estimate of dRPE to regulate aquabiking. Twelve active young subjects performed a pedaling task on an immersed ergocycle using randomly imposed cycling cadences ranging from 50 to 100 rpm in 3-minute steps interspersed by 3-minute active recovery periods. dRPE and cardiorespiratory responses (heart rate [HR]; percentage of heart rate peak value [%HRpeak]; oxygen uptake [VO2]; and percentage of peak oxygen uptake [%VO2peak]) were measured during the last minute of each level. RESULTS: The data described three-step relationships between dRPE and rpm. RPE-chest and RPE-legs increased linearly only for cadences between 60 and 90 rpm (r=0.81 and r=0.88, respectively; P<0.001). At these cadences, significant relationships were also observed between dRPE and all the physiological data (highest Pearson product moment for %VO2peak: 0.81 for RPE-chest and 0.88 for RPE-legs, P<0.0001). Last, the classic signal dominance from the legs was observed (RPE-legs>RPE-chest, P<0.0001) but was reduced compared with data obtained during dryland cycling, suggesting a modulating effect of the aquatic medium. CONCLUSIONS: Cycling cadence was the better estimator of RPE-legs, which seemed to be the more appropriate dRPE to regulate the intensity of aquabiking in a safe range of pedaling rates.